1967
DOI: 10.1128/jvi.1.6.1227-1237.1967
|View full text |Cite
|
Sign up to set email alerts
|

New Assay Procedure for Separation of Mycoplasmas from Virus Pools and Tissue Culture Systems

Abstract: Presence of mycoplasma organisms in tissue culture systems and virus pools was detected by titration of the contaminated material on agarose-suspended BHK21 / 13S cells. The use of this method permitted isolation of mycoplasmas which could not be detected by standard assay methods. Mycoplasma colonies at concentrations ranging from 104 to 106 colony-forming units/ml in agarose-BHK21/13S media could be distinguished from virus plaques, and the two populations of inicroorganisms could be easily disassociated eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1967
1967
1978
1978

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…Hopps et al (1973) identified Mycoplasma hijorhinis in cell cultures by immunofluorescence, though they failed to culture it on agar medium. Similar results were reported by Zgorniak-Nowosielska et al (1967), Schneider et al (1974b) and House and Waddell (1967). Thus, an obvious need for an improved medium for the isolation of mycoplasmas exists.…”
Section: Discussionsupporting
confidence: 85%
“…Hopps et al (1973) identified Mycoplasma hijorhinis in cell cultures by immunofluorescence, though they failed to culture it on agar medium. Similar results were reported by Zgorniak-Nowosielska et al (1967), Schneider et al (1974b) and House and Waddell (1967). Thus, an obvious need for an improved medium for the isolation of mycoplasmas exists.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, an accompanying paper (10) describes the use of this method for the growth of mycoplasma contaminants of virus pools which formed easily visible colonies. This fact enabled us to derive pure rabies and LCM clones from two virus stocks which had become contaminated with mycoplasma (10).…”
Section: Resultsmentioning
confidence: 99%
“…Incorporation of kanamycin, streptomycin, or tylosin into maintenance media did not prevent plaque formation. The plaques formed by agent Y lacked the morphological characteristics recently described for PPLO (7,11), and known cultures of PPLO did not plaque in the systems described above. Adsorption of antisera against agent Y with concentrated preparations of PPLO isolated from contaminated tissue culture did not inhibit the formation of characteristic precipitin patterns in immunodiffusion tests.…”
Section: Fig 3 Precipitin Patterns Formed In Homologousmentioning
confidence: 75%